Avaliação do destreinamento físico nasuscetibilidade à síndrome metabólica em um modelo murino - Albuquerque, Daniela Leonardo de (2018)
The growing number of overweight and obese people, caused by sedentary lifestyle and high-fat eating, appears to be one of the main risk factors for the development of chronic noncommunicable diseases (CDNTs) and has aggravated the cardiovascular and metabolic diseases, such as Metabolic Syndrome (SMet). Thus, in the present study, we attempted to evaluate the effects of physical detraining for the susceptibility to dietary metabolic syndrome in a murine model. Male C57BL / 6 mice aged 10-12 weeks were randomly assigned to four experimental groups: a sedentary control group (CS “chow”) and a detraining group (D"chow") fed a standard diet (Nuvilab® São Paulo - SP, Brazil); a sedentary control group (CS HFD) and a detraining group (DHFD) who initially were fed a standard diet (Nuvilab® São Paulo - SP, Brazil) and later fed a high calorie diet during the detraining period. The training was performed for 4 weeks, 5 days / week, 2 times daily with 90 minutes / session, only by groups D "chow" and D HFD. After the training protocol the twogroups remained 8 weeks in detraining and only the CS HFD and DHFD groups received a hypercaloric diet. At the end of the experimental period, the animals of the D HFD group presented a significant gain in body weight and visceral fat deposition compared to CS HFD and D chow, indicating that detraining accentuates the metabolic effects associated with the hypercaloric diet. At the end of the experiment, fasting glycemia was significantly higher in D HFD compared to the other groups. The consumption of the high fat diet induced glucose intolerance and reduced insulin sensitivity, being more pronounced in the detraining group (D HFD). The plasma lipid profile showed increased cholesterol in the CS HFD and D HFD groups; the triglycerides and VLDL were not different between the groups; there was a decrease of the NEFA in the Dchow group compared to the CS chow. Associated with increased liver mass, the liver lipid profile showed a significant increase in cholesterol, VLDL fraction and triglycerides in the detraining group (D HFD vsCS HFD, D HFD vsD"chow"). On the other hand, there was a decrease in VLDL and triglycerides in the detraining group D "chow" compared to sedentary CS "chow" (D"chow" vs. CS "chow"). However, there was no difference between groups for hepatic AGNE levels. In the histological analysis of the liver, qualitative lipid deposition was observed for micro and macro fat vacuoles only in the D HFD group, and for micro vacuoles in the CS HFD. The markers of ALT and AST liver damage, as well as the AST / ALT ratio, did not show significant changes in either group. The systemic and hepatic activity of the enzyme catalase did not present significant alteration in any of the experimental groups, as well as the hepatic activity of the enzyme arginase. In view of the results obtained, it is concluded that the ingestion of hypercaloric foods during the detraining period is an aggravating factor to the development of obesity, which in the long term may favor the appearance of hepatic steatosis and, to a greater degree, SMet.